Uso de Metilergonovina y su Relación con el Momento de Administración en Parturientas del Hospital Regional de Loreto Iquitos 1994 - Becerril Ibérico, Carmen Yisela (1994)
This study experimentally APPLIED type level was conducted at Hospital Regional de Loreto - Iquitos, in the year 1,994, in order to meet the need of using Methylergonovine and time of administration; for this purpose the classical experimental design was used, in which three study groups were taken, one experimental A2 - A3 (administration Methylergonovine 1 ampoule of 0.2 mg intramuscularly to deliver the fetus to the A2 group and out of the placenta. for group A3), then 0.125 mg orally every 8 hours to 24 hours, recording a total of 165 patients with parity 1-5, 55 for each group. After performing the appropriate testing of the hypothesis was reached the following results: The volume control bleeding B1 group was 376 cc., For the experimental group A2 was 365.9 cc., And the A3 group 409.8 cc., Relatively higher loss in multiparous than primiparous. The average uterine involution the seventh day in group B1 was 6.29 cm .; in loc experimental groups (A2 - A3) 4.52 and 5.72 cm. respectively, the latter responding better multipare while shortening the delivery period 7.53 minutes recorded in the patients of group A2. Major complications are bleeding and presented subinvolution, meeting for the first 11 patients and twelve for the second, mostly multiparous, with minor complications such A2 group. These results demonstrated that the best time to implement the Methylergonovine is to deliver the fetus (experimental group A2) and its use should not be routine but with a prior assessment of risk factors such as high parity, hydramnios, and twinship.